Smart switch board: solution for reliability and power management - Islam, Mahmudul; Siddiqui, Monoarul Alam; Ehtesum, Md. (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.